Hubungan Pengetahuan dan Sikap terhadap Kinerja Perawat dalam Pendokumentasian ASKEP di RSUD I Lagaligo Wotu - Evi Kurniasari; M. Irsan Arief Ilham (Nutrition Science and Health Research, 2022)
Nursing documentation is a permanent record of what happened to the client. Apart from being an accreditation requirement which is a legal requirement in health services (Doenges, 2013). One of the functions of documentation for nurses is as a means of communication and evidence of accountability for the implementation of care activities (Ministry of Health of the Republic of Indonesia, 2013). To find out the relationship between knowledge and attitudes towards nurse performance in documenting nursing care at RSUD I Lagaligo Wotu in 2021. The research design used is an analytical survey with a correlational type of study. The approach used in this study was a cross-sectional approach with a total of 84 nurses and sampling using accidental sampling techniques. Data collection using questionnaires and data processing using the SPSS 22.0 program presented in the form of tabels and narratives. The analysis carried out is univariate and bivariate with a meaningfulness level of α = 0.05. The results of the data analysis obtained that there was a relationship between knowledge and the performance of nurses in the completeness of documenting nursing care at RSUD I Lagaligo Wotu.